(untitled) (Jurnal Manajemen Teknologi, 2025)
Abstract. Digitalization is an important thing for companies today. Many start-ups utilize technology to improve efficiency, flexibility, and connectivity in various aspects of business. The Indonesian Information and Communication Technology Creative Industry Society (MIKTI) said that the development of start-ups that utilize digital technology in Indonesia is very high and experiencing rapid growth (Rahman, 2024). Indonesia ranked sixth globally at the beginning of 2024 in terms of the highest number of start-ups, totaling 2,562, while Jakarta was recognized as the city with the second-best start-up ecosystem at the global Top Emerging Ecosystem level (Startupranking, 2024). The millennial generation is one of the generations that will fill important positions in companies in the future, a generation that is close to technology, they are often called "Digital Natives". However, this generation has low work engagement, which is in line with the problems with human resources (HR) experienced by the start-up industry. This study aims to test the effect of transformational leadership on work engagement through psychological empowerment as a mediator carried out on millennial generation employees of start-ups in DKI Jakarta. This study uses a quantitative research design with a questionnaire distribution. A total of 203 respondents were analyzed using AMOS 21 to test the research hypothesis. The results showed that transformational leadership has a positive effect on work engagement. In addition, the psychological empowerment variable mediates the effect of transformational leadership on work engagement. Keywords: Transformational leadership, work engagement, psychological empowerment